Prevalence of anisometropia and associated factors in Shandong school-aged children - Xu, Zihang; Wu, Ziyun; Wen, Ying; Ding, Meihua; Sun, Wei; Wang, Yirong; Shao, Zhen; Liu, Yi; Yu, Mingkun; Liu, Guoyong; Hu, Yuanyuan; Bi, Hongsheng (Frontiers in Public Health, 2022)
Objective: To investigate anisometropia's prevalence and associated factors in school-aged children. Methods: A cross-sectional school-based study was conducted in Shandong Province, China, including children aged 4 to 17 from 9 schools. Anisometropia was defined as the differences between the two eyes in spherical equivalent (SE) or cylinder degree of 1.00 diopter (D) or more [SE or cylindrical (CYL) difference≥1.00D] after cycloplegic autorefraction. The Generalized Linear Model (GLM) was used to analyze the effects of ocular parameters [the differences between eyes in axial length (AL), habitual visual acuity (HVA), and corneal astigmatism (CA)] and lifestyle parameters (time spent indoor near work and outdoor activities) on anisometropia. Results: Total 4,198 (93.4%) of the 4,494 children were included in the statistical analysis. The mean difference in inter-eye SE was 0.42±0.61D. The prevalence of anisometropia was 13.2% (95%CI: 12.1% to 14.2%) (SE anisometropia’s prevalence:10.3%; CYL anisometropia’s prevalence: 4.1%), increased with older age (OR=1.10, P=0.002), the worse myopic eye (myopia versus premyopia, OR=1.87, P=0.002), the worse hyperopic eye (hyperopia versus premyopia, OR=1.77, P=0.013), larger difference in inter-eye AL (0.1-0.3 versus ≤0.1, OR=1.67, P=0.008; >0.3 versus ≤0.1, OR=28.61, P<0.001), HVA (>0.2 versus ≤0.2, OR=3.01, P<0.001), CA (OR=6.24, P<0.001), the worse stereoacuity (>100 versus ≤100, OR=1.59, P=0.001), longer indoor near work time per day on weekends (4-8 versus <4, OR=1.41, P=0.038; ≥8 versus <4, OR=1.40, P=0.131), and shorter outdoor activity time per day on weekdays (≥1 versus <1, OR=0.75, P=0.046) in multivariable analysis. In the SE anisometropia group, the difference in inter-eye AL (>0.3 versus ≤0.1, β: 0.556, 95%CI: 0.050 to 1.063), HVA (>0.2 versus ≤0.2, β: 0.511, 95%CI: 0.312 to 0.710), and CA (β: 0.488, 95%CI: 0.289 to 0.688), stereoacuity (>100 versus ≤100, β: 0.299, 95%CI: 0.110 to 0.488) had a positive impact on the difference in inter-eye SE. Conclusions: Ocular parameters and lifestyle parameters are associated with the occurrence of anisometropia in children aged 4 to 17 years, including the difference in inter-eye AL, HVA, CA, stereoacuity, indoor near work time, and outdoor activity time. Preventing myopia and early treating anisometropic amblyopia may be effective ways to reduce the prevalence of anisometropia.